Review on Illegal Wildlife Trade Provisions in Indonesia: Cost-Benefit Analysis and Law Enforcement - Eryan, Adrianus (Indonesian Journal of International Law, 2024)
Illegal wildlife trade is a crime that is rarely systematically exposed and difficult to investigate but generates extraordinary profits. As a one of mega biodiversity country in the world, Indonesia is an easy target for illegal wildlife trade. Unfortunately, existing law enforcement practices still need to be improved. There are at least two supporting factors enabling the wildlife crime: inadequate normative legal basis and weak law enforcement resulting from the high cost of crimes. The research is carried out through a series of theoretical frameworks of cost-benefit analysis and criticisms regarding ideal law enforcement practices through various court decisions. At the time of this writing, the Conservation of Biodiversity and Ecosystems Act Number 5 Year 1990 is also in the revision process in the parliament. Thus, this article argues three crucial revision points: promoting the recognition of illegal wildlife trade as a transnational organized crime, increasing the cost of the crime, and proposing restoration-oriented law enforcement to promote concrete and positive impacts to the sustainability of wildlife, ecosystems, and biodiversity.